Delivery of Mycobacterium tuberculosis epitopes by Bordetella pertussis adenylate cyclase toxoid expands HLA-E-restricted cytotoxic CD8+ T cells - Badami, Giusto D.; La Manna, Marco P.; Di Carlo, Paola; Stanek, Ondrej; Linhartova, Irena; Caccamo, Nadia; Sebo, Peter; Dieli, Francesco (Frontiers in Immunology, 2023)
Introduction Tuberculosis (TB) remains the first cause of death from infection caused by a bacterial pathogen. Chemotherapy does not eradicate Mycobacterium tuberculosis (Mtb) from human lungs, and the pathogen causes a latent tuberculosis infection that cannot be prevented by the currently available Bacille Calmette Guerin (BCG) vaccine, which is ineffective in the prevention of pulmonary TB in adults. HLA-E-restricted CD8+ T lymphocytes are essential players in protective immune responses against Mtb. Hence, expanding this population in vivo or ex vivo may be crucial for vaccination or immunotherapy against TB. Methods The enzymatically inactive Bordetella pertussis adenylate cyclase (CyaA) toxoid is an effective tool for delivering peptide epitopes into the cytosol of antigen-presenting cells (APC) for presentation and stimulation of specific CD8+ T-cell responses. In this study, we have investigated the capacity of the CyaA toxoid to deliver Mtb epitopes known to bind HLA-E for the expansion of human CD8+ T cells in vitro. Results Our results show that the CyaA-toxoid containing five HLA-E-restricted Mtb epitopes causes significant expansion of HLA-E-restricted antigen-specific CD8+ T cells, which produce IFN-γ and exert significant cytotoxic activity towards peptide-pulsed macrophages. Discussion HLA-E represents a promising platform for the development of new vaccines; our study indicates that the CyaA construct represents a suitable delivery system of the HLA-E-binding Mtb epitopes for ex vivo and in vitro expansion of HLA-E-restricted CD8+ T cells inducing a predominant Tc1 cytokine profile with a significant increase of IFN-γ production, for prophylactic and immunotherapeutic applications against Mtb.